(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Abstract Liver transplantation is an ultimate procedure in patients suffering end-stage liver diseases. In these last years the donation after cardiac death (DCD) has increased the pool of potential liver donors. Different studies and procedures are involved in the prevention of the main ischemic problems during the reconditioning and resuscitation of the marginal livers. Normothermic extracorporeal liver perfusion (NELP) avoids prolonged cold storage damage that is the main cause of steatosis and biliary tract ischemia in transplanted patiens. Different porcine models have been studied and developed to understand the ischemia mechanism and to select the better technique for NELP. We conducted our study using a DCD pig liver model collected from slaughterhouse. Using extracorporeal membrane oxygenation, 2000 ml of total fluid containing autologous blood, lidocaine, heparin, antibiotics, glucose 10 % solution and flunixin, the NELP was achieved. The liver was perfused over 7 hours after 48 hours of cold storage (4C°), using Eurocollins solution. During the liver withdrawal in the slaughterhouse 20 minutes were waited to simulate the warm ischemia (WI) time. Histological samples, swab for bacterial grow, blood sample, temperature and pulse oximetry saturation were collected to assess the liver viability and function. These analyses revealed stable metabolism throughout perfusion identifying a cycles 2 hours length, coinciding with recovery of oxygen uptake rates to fresh liver, as described in literature. In summary the preliminary established model of isolated hemoperfused slatherhouse liver reveals the important role of the relation between cold storage and normothermic perfusion. Moreover this preliminary study justifies further investigation of the optimization of the treatment protocols and perfusion media.